2013
DOI: 10.1186/cc12711
|View full text |Cite
|
Sign up to set email alerts
|

Blockade ofthe negative co-stimulatory molecules PD-1 and CTLA-4 improves survival in primary and secondary fungal sepsis

Abstract: IntroductionFungal sepsis is an increasingly common problem in intensive care unit patients.Mortality from fungal sepsis remains high despite antimicrobial therapy that is highly active against most fungal pathogens, a finding consistent with defective host immunity that is present in many patients with disseminated fungemia.One recently recognized immunologic defect that occurs in patients with sepsis is T cell "exhaustion" due to increased expression of programmed cell death -1 (PD-1).This study tested the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
208
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(234 citation statements)
references
References 39 publications
6
208
0
3
Order By: Relevance
“…significant changes in splenic T-cell IFN-g production were found in mice treated with either anti-PD-1 or anti-CTLA-4 antibodies (32).…”
Section: Ctla-4mentioning
confidence: 90%
“…significant changes in splenic T-cell IFN-g production were found in mice treated with either anti-PD-1 or anti-CTLA-4 antibodies (32).…”
Section: Ctla-4mentioning
confidence: 90%
“…Recent studies demonstrated neutrophil PD-L1 upregulation on neutrophils from septic mice and humans, resulting in the potentiation of lymphocyte apoptosis through contact inhibition, which correlated with outcome (117). Moreover, in clinically relevant animal models of bacterial sepsis, inhibition of PD-1 and PD-L1 signaling improved survival and reduced the incidence of fungal infections (118). Considering the beneficial impact on adaptive immunity and tumor eradication strategies, it makes sense that PD-1 and PD-1L could concomitantly serve as biomarkers of sepsis-initiated immune suppression as well as prospective therapeutic targets to reverse adaptive immune dysfunction and improve long-term survival.…”
Section: Potential Immune-modulatory Therapiesmentioning
confidence: 99%
“…Brahmamdam et al (43), using a novel therapeutic strategy, reported that an anti-PD-1 antibody administered 24 h after cecal ligation and puncture prevented the sepsis-induced depletion of lymphocytes and dendritic cells and improved survival. More recently, Chang and collaborators (40) reported that the blockade of PD-1 and CTLA-4 by the respective antibodies improved survival in a Candida-challenged sepsis mouse model. Ceftriaxone-plus-azithromycin combination therapy may involve an optimal modulation of CTLA-4 and PD-1 expression to restore immune functions and contribute to enhanced survival in a mouse model of lethal pneumococcal pneumonia.…”
Section: Cd11cmentioning
confidence: 99%
“…Nearly four decades of investigating anti-inflammation strategies against sepsis, based on the concept that excessive inflammation might be the main cause for the adverse outcomes of sepsis, have yielded disappointing results. However, there is now evidence that the immunosuppressive state involves a misbalance between proinflammatory reactions and anti-inflammatory responses following the initial hyperinflammation state in sepsis, which may contribute to the high mortality of sepsis (16,17,40). Among several target molecules that have been proposed to overcome the immunosuppressive state in sepsis patients, most attention has been focused on immune checkpoint receptors such as PD-1 and CTLA-4 as promising molecules, based on several clinical and experimental findings.…”
Section: Cd11cmentioning
confidence: 99%